Analysis of Microbial and Physio-Chemical Attributes in Fresh, Sun-Dried, and Oven-Dried Tomatoes (Solanum Iycopersium) - Omorodion, Nnenna Jennifer; Richmas Obiobu, Euboniso (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
This study accessed the microbial and physiochemical qualities of fresh, oven-dry, and sun-dry tomatoes to comprehensively understand the impact of drying methods on the quality and safety of this widely consumed fruit. Microbial and physiochemical analysis were done using standard methods. It revealed the variations in microbial population with the results showing the total viable bacterial count ranged from 1.3×106cfu/g to 2.7×106cfu/g with fresh tomato (FT) slices having the highest value (2.7×106cfu/g). Sun-dried tomatoes (SD) (2.3×106cfu/g), oven-dried at 40°C (1.6×106cfu/g) and oven-dried at 60°C (1.4×10-6cfu/g) respectively. The least count was obtained from sample oven-dried (OVD) at 80°C (1.3×106cfu/g). The total viable fungal count the fresh tomato (FT) slices had the highest counts (2.6 ×104cfu/g) and the least count was obtained from sample oven-dried at 40°C (6×103cfu/g), highlighting the dynamic microbial changes during different drying processes. Additionally, physiochemical assessments encompassed proximate compotion, pH and ascorbic acid levels. The pH range was between 4.1 (for fresh tomatoes) and 5.2 (for sun-dried tomatoes). Ascorbic acid levels also showed Fresh tomatoes (28.32mg/100g) were the highest but in this case, Oven-dried at 80°C had the least (9.21mg/100g). Notable differences emerged, shedding light on the consequences of drying techniques on key quality indicators. In conclusion, this study provides a comprehensive analysis of the microbial and physiochemical properties of fresh, oven-dry, and sun-dry tomatoes, elucidating the impact of various drying methods on the quality and safety of this widely consumed fruit. More so, the observed variations in physiochemical properties suggest the need for careful consideration of other drying methods such as vacuum drying and freeze-drying to preserve flavor, enhance shelf life, and maintain nutritional quality.